Pharmacokinetic and pharmacodynamic evidence of adrenaline administered via auto‐injector for anaphylactic reactions: A review of literature. Issue 3 (8th July 2020) - Moss, James; Jani, Yogini; Edwards, Brian; Tomlin, Stephen; Rashed, Asia N.
Abstract : Anaphylaxis is a severe allergic reaction that can lead to death if not treated quickly. Adrenaline (epinephrine) is the first‐line treatment for anaphylaxis and its prompt administration is vital to reduce mortality. Following a number of high‐profile cases, serious concerns have been raised, both about the optimal dose of intramuscular adrenaline via an auto‐injector and the correct needle length to ensure maximal penetration every time. To date, the public data are sparse on the pharmacokinetics–pharmacodynamics of adrenaline administered via an auto‐injector. The limited available literature showed a huge variation in the plasma concentrations of adrenaline administered through an auto‐injector, as well as variations in the auto‐injector needle length. Hence, delivering an effective dose during an anaphylaxis remains a challenge for both patients and healthcare professionals. Collaborative work between pharmacokinetics–pharmacodynamics experts, clinical triallists and licence holders is imperative to address this gap in evidence so that we can improve outcomes of anaphylaxis. In addition, we advise inclusion of expertise of human factors in usability studies given the necessity of carer or self‐administration in the uniquely stressful nature of anaphylaxis.